2001
DOI: 10.1002/cne.1336
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cocaine‐ and amphetamine‐regulated transcript peptide in the guinea pig intrinsic cardiac nervous system and colocalization with neuropeptides or transmitter synthetic enzymes

Abstract: This study was conducted to establish the presence of cocaine- and amphetamine-regulated transcript peptide (CARTp) immunoreactivity in neurons and fibers within guinea pig atrial whole-mount preparations containing the intrinsic cardiac ganglia. Many cardiac ganglia, but not all, in a given whole-mount preparation, were innervated by CARTp-immunoreactive (IR) fibers. Following explant culture of whole mounts for 72 hours, the CARTp-IR fiber networks were absent, but the number of CARTp-IR neurons was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
0
23
1
Order By: Relevance
“…We did not attempt to establish colocalization of NOS and TRPC6 in sections of nodose ganglia doubly labeled using the sheep antiserum directed against NOS. As indicated previously, the sheep antiserum directed against NOS did not consistently label cells above background in sections of nodose ganglia (Calupca et al, 2001).…”
Section: Trpc6-ir Cells Are Present In Vagal Afferentmentioning
confidence: 94%
“…We did not attempt to establish colocalization of NOS and TRPC6 in sections of nodose ganglia doubly labeled using the sheep antiserum directed against NOS. As indicated previously, the sheep antiserum directed against NOS did not consistently label cells above background in sections of nodose ganglia (Calupca et al, 2001).…”
Section: Trpc6-ir Cells Are Present In Vagal Afferentmentioning
confidence: 94%
“…CART was found primarily in the brain, but is also present in the plexuses of the stomach muscular layer of mammals, e.g. in pig and wild boar (where it coexists with other biologically active neuropeptides, such as GAL, SP, and NPY) [27], sheep [28], various parts of rat's gastrointestinal [10], intramural ganglia of the pig urinary bladder in colocalization with pituitary adenylate cyclase-activating polypeptide (PACAP) [29] and in cardiac ganglia of a number of animals, including guinea pig and rat [30][31][32]. In the enteric nervous system CART is regarded as a strong neuroprotective factor.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies describing the presence of cocaineand amphetamine-related transcript peptide (CART) proteins in cardiac ganglia have been conducted recently [10,18,19,53,54,58]. The CART neuropeptide is also known as an anorexigen from other areas in the nervous system, mostly the hypothalamus, although there is an increasing number of reports of yet another function as a neurotransmitter in the ANS.…”
Section: Neurochemical Characteristic Of Cardiac Gangliamentioning
confidence: 99%
“…In guinea pigs, CART was found in vagus nerve endings in the heart and when it was injected in the solitary tract nucleus, baroreflex was impaired and bradycardia ensued [58]. Calupa et al [10] demonstrated that most (but not all) cardiac ganglia in guinea pigs were innervated by nerve fibres immunoreactive to CART. Only few neurocytes in cardiac ganglia were positive to CART.…”
Section: Neurochemical Characteristic Of Cardiac Gangliamentioning
confidence: 99%